Empowering teachers: The impact of transformational leadership and teacher competence on performance through organizational commitment - Soelistya, Djoko (UIN Raden Mas Said Surakarta, 2024)
The success of education is largely determined by the performance of quality teachers in planning, implementing, and evaluating learning, maintaining task discipline, and being active in the classroom. This study examined the interrelationships between transformational leadership style, teacher competence, organizational commitment, and teacher performance within educational environments. This quantitative study used the SmartPLS software with the bootstrapping method. A questionnaire was used to collect data from the 75 participants. Transformational leadership has a significant influence on both teacher and organizational commitment. Although competence positively influences organizational commitment, it does not affect teacher performance. Likewise, organizational commitment does not affect teacher performance. Furthermore, Transformational Leadership did not significantly affect Teacher Performance through Organizational Commitment. Similarly, Teacher Competence does not have a significant effect on teacher performance through Organizational Commitment. Understanding these dynamics could enhance strategies for improving teacher effectiveness and organizational outcomes in educational settings. The findings contribute both practically, by informing leadership practices and teacher development programs, and theoretically, by advancing the understanding of the complex relationships among leadership, competence, commitment, and performance in educational contexts.